PENERAPAN PENDEKATAN GENRE BASED DALAM KETERAMPILAN MENULIS BAHASA ASING: SEBUAH TINJAUAN PUSTAKA - MGS. A. Gebby Al Muhar; Shafa Amira Fauziah; Dante Darmawangsa; Dadang Sunendar; Angginaaken Nurani (FKIP, Universitas Palangka Raya, 2023)
The application of approaches in foreign language learning has become related to the learning process in recent years. Genre-based approach is an approach in language learning that focuses on the understanding and production of texts based on genres and is commonly used for learning writing skills. This study aims to describe the results of thematic literature review on the effect of Genre-based approach on the development of learners' writing performance, the challenges faced by teachers and learners in the implementation of Genre-based approach, and learners' perspectives on genre-based approach for foreign language writing skills. This research uses a thematic literature review method by reviewing scientific research articles related to the topic discussed. The articles were selected through Google Scholar and Researchgate channels in the last 5 years since this research was conducted with 30 articles that met the set criteria. The results of this study found that the Genre Based approach to foreign language writing skills has a positive influence in improving writing performance and motivating writing for learners. However, in its implementation, there are challenges in that it takes a lot of time, teachers are less adaptable so that in some cases the results achieved don’t show significant changes.